Extracorporeal Shockwave Therapy Increases Growth Factor Release from Equine Platelet-Rich Plasma In Vitro - Seabaugh, Kathryn A.; Thoresen, Merrilee; Giguère, Steeve (Frontiers in Veterinary Science, 2017)
Introduction Extracorporeal shockwave therapy (ESWT) and platelet rich plasma (PRP) are common treatments for soft tissue injuries in horses. Shockwave triggers cell specific responses to promote healing. Growth factors released from PRP also promote healing. It has been hypothesized that greater growth factor release would amplify the healing process. The combination of extracorporeal shockwave therapy and platelet rich plasma could promote healing in injured tendons and ligaments in the horse. The objective of this study was to determine if application of shockwaves to platelet rich plasma samples increases the concentration of Transforming Growth Factor B1 (TGF-B1) and Platelet Derived Growth Factor BB (PDGF-BB) released from the platelets in vitro. Materials and methods Platelet rich plasma was produced from blood drawn from 6 horses. The PRP from each horse was exposed to the following treatments: 1) positive control (freeze-thaw cycle), 2) untreated negative control, or shockwaves with either 3) a “standard probe” (ESWT-S) with a 2cm focal width and medium energy density or 4) a “power probe” (ESWT-P) with a 1cm focal width and high energy density. After each treatment, the samples were centrifuged and the supernatant was harvested. The supernatant was then used for growth factor quantification via commercially available ELISA kits for TGF-B1 and PDGF-BB. Results Concentrations of TGF-B1 and PDGF-BB in PRP that underwent a freeze thaw cycle were significantly increased compared to all other treatments. Both ESWT-S and ESWT-P resulted in significantly increased TGF-B1 concentrations, 46% and 33%, respectively, when compared to the negative control. Both ESWT-S and ESWT-P resulted in significantly increased PDGF-BB concentrations, 219% and 190%, respectively, when compared to the negative control. Discussion This data indicates that the application of extracorporeal shockwave therapy to platelet rich plasma increases the expression of growth factors in vitro. This suggests that the combination therapy of local PRP injection followed by ESWT may stimulate release of growth factors from platelets after they have been injected into the area of injury. Conclusion The combination of PRP and ESWT might result in synergism of two modalities previously utilized individually for tendon and ligament injuries in horses.